Chain length dependent olefin re-adsorption model for Fischer-Tropsch synthesis over Co-Al2O3 catalyst - Bhatelia, Tejas; Li, C.; Sun, Y.; Hazewinkel, P.; Burke, N.; Sage, V. (Elsevier, 2014)
Many models for describing the Fischer-Tropsch synthesis (FTS) over supported cobalt catalysts have been postulated but there is still much debate over its mechanisms and governing physio-chemical phenomena, particularly those relating to secondary reactions of olefins. In this work, a comprehensive kinetic model for the FTS over Co/Al 2 O 3 catalyst, was developed to provide mechanistic explanations for deviations from Anderson-Schulz Flory (ASF) distributions. Experiments were conducted in a fixed bed reactor over a wide range of operating conditions (T = 483-493 K, P = 1.5-2 MPa, feed ratio H 2 /CO = 1.4-2.1 and CO conversion X CO = 15-75%). Models were developed using, carbide, enolic and CO insertion mechanisms. The concept of 1-olefin re-adsorption and its chain length dependency was introduced. Chain length dependency was assumed to be due to an increased probability of 1-olefin interaction with the active site, with an increasing carbon number. Model results were analysed for statistical and physio-chemical robustness. The calculated apparent activation energies for the selected model were in good agreement with the values reported in the literature. It was found that FTS proceeded via the CO insertion mechanism and chain length dependent 1-olefin re-adsorption phenomena primarily governed the deviations from ASF distributions. Â© 2014 Published by Elsevier B.V. All rights reserved.